2020
DOI: 10.2147/cia.s239053
|View full text |Cite
|
Sign up to set email alerts
|

<p>Examination of the Correlation Between Physical and Psychological Measures in Community-Dwelling Older Adults</p>

Abstract: Introduction: The purpose of this study was to determine if correlations exist between strength and mobility and psychological measures of anxiety and depression in communitydwelling older adults. Methods: One hundred and eleven participants randomly completed trials of grip strength (GS), the Timed Up and Go (TUG), the 10-meter walk test (10MWT), the Geriatric Anxiety Scale (GAS), and the Geriatric Depression Scale (GDS) in a prospective, correlational study. Results: This study found significant correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
2
7
0
2
Order By: Relevance
“…This means that an increase in the TUG time is associated with higher scores in the GDS; in other words, poorer physical performance in the TUG would be related to higher levels of depression. Staples, Kays, and Richman [ 50 ], and APRN-CNP and Noonan [ 51 ] agreed with our results, finding a small direct correlation (r = 0.25 and r = 0.23, respectively) between these variables. Their interventions were carried out in populations of older adults and older women diagnosed with breast cancer, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…This means that an increase in the TUG time is associated with higher scores in the GDS; in other words, poorer physical performance in the TUG would be related to higher levels of depression. Staples, Kays, and Richman [ 50 ], and APRN-CNP and Noonan [ 51 ] agreed with our results, finding a small direct correlation (r = 0.25 and r = 0.23, respectively) between these variables. Their interventions were carried out in populations of older adults and older women diagnosed with breast cancer, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Some authors reported how depression could be considered not only a consequence but also a risk factor for frailty (i.e., Robertson et al, 2013 ). Particularly, a decrease in handgrip strength was associated with an increased depressive symptomatology (Brooks et al, 2020 ), which seemed also to be a predictor of slow walking speed (Staples et al, 2020 ). Another study showed that higher levels of depression and anxiety were associated with a slowdown in gait speed in subjects aged 65 and older with atrial fibrillation (Marino et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quanto ao desempenho no Timed Up and Go, os resultados obtidos estiveram de acordo com outros estudos (4,8,15,21) que revelaram alteração de equilíbrio dinâmico entre 60,0 a 80,0% em idosos da comunidade, sendo que este percentual pode superar 90,0% quando avaliados idosos institucionalizados (24) . Pesquisas apontaram a relação de maior tempo dispendido no teste, sugestivo de comprometimento do equilíbrio dinâmico, com o relato de quedas e idade (4,15) .…”
Section: Discussionunclassified